Membrane distillation crystallization-performance enhancement and scaling control - Chen, Guizi (2015)
Membrane distillation (MD) is well recognized as a potential alternative technology for desalination due to the benefits of moderate operating temperatures, low sensitivity to feed salinity, high salt rejection and ability to incorporate free lowgrade heat. However, technical challenges that impede the industrialization of MD brine processing still remain, which include the temperature polarization effect and fouling/scaling formation, especially at high salt concentration, etc. This thesis provides a comprehensive review on the state-of-art of MD operations in concentrated solutions, focusing on some areas that need to be further investigated or improved, such as available methods for performance enhancement and scaling control in membrane processes, investigation and measurement of membrane fouling/scaling, the coupled processes of membrane and crystallization operations, which may provide strategies to address the above challenges. Firstly, the potential of introducing gas bubbling has been preliminary explored to improve fluid dynamics and shear stress in the shell side of the DCMD module. The effect of operating conditions and module configuration on the flux enhancement ratio induced by gas bubbling were investigated in a low concentration (3.5%) DCMD. Additionally, the module performance and scaling status for high salt concentrations (from 18% to supersaturation) have been examined and compared in three systems (i.e., modified module with knitted-spacers, original modules with and without bubbling). It was found that the introduction of gas bubbling not only mitigates the temperature polarization effect but also enhances surface shear stress intensity to postpone scaling formation on the membrane surface. Secondly, a more in-depth theoretical analysis on the working mechanisms of gas bubbling was studied, with the aid of direct observation and statistical analysis on the bubble characteristics. The results showed that bubbles with small mean size and narrow size distribution were preferred for creating even flow distribution, intensifying mixing and enhancing surface shear stress. Compared to that of a nonbubbling DCMD system, the values of heat transfer coefficient and temperature polarization coefficient (TPC) reached up to 2.30- and 2.13-fold, respectively, at an optimal gas flowrate. Additionally, with the theoretical expressions for scaling resistance derived based on resistance-in-series model, it was found that gas bubbling can remarkably decrease scaling resistance, due to the high shear stress induced by the flowing water and gas bubbles. Thirdly, fundamentally, in order to prevent scaling formation and prolong membrane lifespan, a novel method was proposed to quantify the scaling formation in DCMD brine concentration processes, based on crystal kinetics on the membrane surface and transfer mechanisms of MD. A mathematical model, namely, crystallization on membrane surface (COMS), was developed and verified in terms of MD performance (critical point of major flux decline and scaling formation) and deposited crystal characteristics (median size and total number). The results indicated that the critical point can be estimated precisely based on COMS model and the scaling information can be quantified effectively by crystallization kinetics. A good agreement with an acceptable average absolute relative error of 10% between the experimental and simulated data confirms the reliability of this proposed COMS model.Fourthly, a hybrid process that integrates MD with crystallization, namely continuous membrane distillation crystallization (CMDC), was systematically studied with a highly concentrated NaCl feed solution (26.7 wt% salt). In order to improve the product recovery (pure water and NaCl crystal) and better realize zero discharge, an orthogonal fractional factorial (OFF) experiment design was used to optimize the operating conditions. The range analysis of the experimental results identified the feed and permeate-side flow rates as the most influential factors affecting CMDC performance. Additionally, the optimal operating parameters determined from the analysis were validated experimentally, which confirmed the merits of the OFF experiment design and analysis for the CMDC process.